The effect of foreign ownership on stock return volatility, with government ownership as a moderator - Nugroho Sasikirono; Mega Rizki Febriana; I made Sudana; Harlina Meidiaswati (Journal of Innovation in Business and Economics, 2020)
This research aims to determine the relationship between foreign institutional ownership and the stock return volatility, as well as the moderating effect of the state-owned enterprises on this relationship. This study uses two proxies of return volatility, namely total and idiosyncratic volatility. The research sample was determined by the purposive sampling method and analysis was conducted by OLS and moderated regression analysis. The number of samples in this study was 181 companies with 342 observations of data for the period 2014-2018. The analysis shows that share ownership by foreign institutional investors has a significant negative effect on the total and idiosyncratic return volatility. Ownership of shares by the government in state-owned enterprises has a moderating effect on such a relationship. The control variables of trading turnover and book-to-market ratio show a significant effect on volatility. Meanwhile, other control variables, which include ownership by domestic institutional and individual investors and free float ratio, do not show the effect on both total and idiosyncratic volatility. Robustness checks by quantile regression come into the same results. The results indicated the important role of foreign investors in the Indonesian capital market in providing market stability and thus stimulating investment climate.